Homozygous deletion of RAG1, RAG2 and 5′ region TRAF6 causes severe immune suppression and atypical osteopetrosis. Issue 6 (19th March 2017) - Weisz Hubshman, M.; Basel‐Vanagaite, L.; Krauss, A.; Konen, O.; Levy, Y.; Garty, B.Z.; Smirin‐Yosef, P.; Maya, I.; Lagovsky, I.; Taub, E.; Marom, D.; Gaash, D.; et al.
Abstract : Mutations of several genes have been implicated in autosomal recessive osteopetrosis (OP), a disease caused by impaired function and differentiation of osteoclasts. Severe combined immune deficiencies (SCID) can likewise result from different genetic mutations. We report two siblings with SCID and an atypical phenotype of OP. A biallelic microdeletion encompassing the 5′ region of TRAF6, RAG1 and RAG2 genes was identified. TRAF6, a tumor necrosis factor receptor‐associated family member, plays an important role in T cell signaling and in RANKL‐dependent osteoclast differentiation and activation but its role in human OP has not been previously reported. The RAG proteins are essential for recombination of B and T cell receptors, and for the survival and differentiation of these cells. This is the first study to report a homozygous deletion of TRAF6 as a cause of human disease. Abstract : Left picture‐increased radio density of the long bones of the leg and a pathological fracture suggesting osteopetrosis. Right picture‐ after about 45 days, note exuberant femoral callus, metaphyseal widening of the distal femur and proximal tibia, with splaying and fraying.